PENDEKATAN SEMANTIK DALAM PENAFSIRAN AL-QUR’AN:: ANALISIS MAKNA LEKSIKAL, GRAMATIKAL, DAN KONTEKSTUAL - Afnan Mu'adzah; Misnawati Misnawati (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2026)
The semantic approach is one of the linguistic approaches that plays a significant role in Qur’anic exegesis by providing a comprehensive understanding of lexical, grammatical, and contextual meanings. This study aims to explain the concept of the semantic approach, describe its application procedures in Qur’anic exegesis, and analyze its significance in producing more profound and contextual interpretations of the Qur’an. This research employs a qualitative library research method. The data were collected from books, scholarly journals, articles, and other relevant academic sources and analyzed using a descriptive-analytical method based on Toshihiko Izutsu’s semantic approach, focusing on basic meaning, relational meaning, and lexical, grammatical, and contextual analyses. The findings reveal that the semantic approach not only examines the primary meaning of Qur’anic vocabulary but also explores the interrelationship between concepts within the Qur’anic linguistic system, the diachronic and synchronic development of meanings, and their connection to historical and social contexts. The application of this approach to the concepts of tabarruj, al-Muzzammil, and nafs wāḥidah demonstrates that the meanings of Qur’anic verses are shaped by linguistic relations, grammatical structures, and contextual usage. Therefore, the semantic approach contributes to producing more objective, comprehensive, contextual, and relevant interpretations of the Qur’an while preserving its fundamental values in addressing contemporary issues.